English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i am not sure how to do it i need to factor
Is this how i start
(4*x^2)-x=3
If this is it i am not sure how to factor it

2006-11-19 11:05:40 · 5 answers · asked by J39P 1 in Science & Mathematics Mathematics

5 answers

4x² -x = 3
4x² - x - 3 = 0
(4x + 3)(x - 1) = 0
x = -3/4, x = 1

2006-11-19 11:09:16 · answer #1 · answered by Philo 7 · 0 0

Yes that is it and you do need to factor, but you must make it equal to zero first:

4x^2 - x - 3 = 0

FOIL: (4x + 3)(x - 1) = 0

So the answers are x = 1 or x = -3/4

2006-11-19 11:09:30 · answer #2 · answered by hayharbr 7 · 0 0

4x^2 - x = 3 4x^2 - x - 3 = 0 utilising the quadratic formula: x = {-b +/- sq.(b^2 - 4ac)}/2a x = [a million +/- sq.(a million - 4(4)(-3))]/2(4) x = [a million +/- sq.(40 9)]/8 x = [a million +/- 7]/8 x = -3/4, a million - .--

2016-11-25 20:20:17 · answer #3 · answered by ? 4 · 0 0

change to

4x² - x - 3 = 0

then move it to (ax+b)(cx+d)=0 format

i'd guess (but i'm drunk)

(4x +3)(x -1)=0

so x = 1
or x = - 3/4

2006-11-19 11:11:00 · answer #4 · answered by rchlbsxy2 5 · 0 0

i think it is (4-x)^2=3 i just finished doing this in math. good luck

2006-11-19 11:12:37 · answer #5 · answered by Michelle 2 · 0 0

fedest.com, questions and answers